2019
DOI: 10.1101/716530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shaky Scaffolding: Age Differences In Cerebellar Activation Revealed Through Activation Likelihood Estimation Meta-Analysis

Abstract: Cognitive neuroscience research has provided foundational insights into aging, but has focused primarily on the cerebral cortex. However, the cerebellum is subject to the effects of aging. Given the importance of this structure in the performance of motor and cognitive tasks, cerebellar differences stand to provide critical insights into age differences in behavior. But, our understanding of cerebellar functional activation in aging is limited. Thus, we completed a meta-analysis of neuroimaging studies across … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Prior work has also suggested that connectivity between the cerebellum and the cerebral cortex is reduced in ageing (Bernard & Seidler, 2014). This may explain recent data showing age differences in cerebellar engagement across cognitive domains including lobule VI and Crus I/II, the regions observed in our findings (Bernard et al, 2020). The authors hypothesise that fewer cerebellar resources reduce the support of automatic processes based on internal behavioural models (Bernard et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Prior work has also suggested that connectivity between the cerebellum and the cerebral cortex is reduced in ageing (Bernard & Seidler, 2014). This may explain recent data showing age differences in cerebellar engagement across cognitive domains including lobule VI and Crus I/II, the regions observed in our findings (Bernard et al, 2020). The authors hypothesise that fewer cerebellar resources reduce the support of automatic processes based on internal behavioural models (Bernard et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…This may explain recent data showing age differences in cerebellar engagement across cognitive domains including lobule VI and Crus I/II, the regions observed in our findings (Bernard et al, 2020). The authors hypothesise that fewer cerebellar resources reduce the support of automatic processes based on internal behavioural models (Bernard et al, 2020). If that is indeed the case and additional resources are required to compensate for the lack of automatic processing, this may be particularly demanding on executive functions, which may have to engage in compensatory processes.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations